The biogeochemical origins and plant-availability of potentially toxic elements in sediment from the Thames Estuary - Shand, Ishbel (Cranfield University, 2005)
In this thesis I investigate the biogeochemical origins and plant availability of potentially toxic elements (PTEs) in sediments dredged from the Thames Estuary. The sediments were pumped from the Thames into silt lagoons on the Rainham Marshes between 1961 and the late 1970s. They are fine-textured and rich in organic matter. The results show that PTE concentrations in the sediments are strongly positively correlated with nitrogen concentrations, and are highly inter-correlated. It is known that this distribution pattern is restricted to ancient and modern sediments from near coastal environments, and hence a link with estuarine processes is suggested. Subsequent investigation showed that the dredgings came from the Thames maximum turbidity zone, and that the lagoons represent a chronological record of changes in sediment quality during a period when dissolved oxygen in the water column rapidly increased. Analysis of one 5 m core from a lagoon showed that there were concurrent substantial changes in the relative proportions of clay, silt and sand in the sediment A novel mechanism is proposed, whereby the textural changes and PTE/organic matter correlation result from mineral dissolution and re-precipitation within flocs in the water column of the maximum turbidity zone. This is mediated by microbial consortia, and is driven by the requirement for Fe(III) as a terminal electron acceptor by dissimilatory iron-reducing bacteria. Potentially toxic elements released from mineral carrier phases are subsequently complexed by various components of the organic fraction or incorporated into secondary minerals and evenly distributed throughout the sediment by tidal action. Published data from historical, geological, hydrological and microbiological science are presented in support of this hypothesis. Foliar concentrations of PTEs in plants grown in the sediments were lower than those predicted by current models, probably because of strong sorption of these elements on sediment solids.